A NEW GENUS OF THE ERINACEIDAE (INSECTIVORA, MAMMALIA) FROM THE OLIGOCENE OF MONGOLIA - Lopatin A.V. (My University, 2003)
On the basis of an almost complete skull with the lower jaw from the Oligocene Shand-Gol Formation of the Ulan-Khureh locality in Mongolia, a new erinaceid genus and species, Scymnerix tartareus, is described. This is a small hedgehog whose skull is approximately 3 cm long. Scymnerix shows convergent similarity to short-faced hedgehogs (Brachyericinae) in certain cranial and dental traits, such as the shortened facial region of the skull, high and raised posterior part of the zygomatic arch, single-rooted I3, the absence of M3, the structure of P4-M2, strongly enlarged I2, and the presence of enamel sculpture on the labial surface of teeth. However, the basicranium structure of Scymnerix suggests that it should be referred to true hedgehogs (Erinaceinae). Structural cranial and dental features of Scymnerix clearly distinguish it from both Amphechinini and Erinaceini and enable one to rank this genus as a separate tribe, Scymnericini tr. nov.
Keywords: Hedgehogs; Erinaceidae; new taxa; Oligocene; Mongolia; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен